Human Security and Development in Africa: An Overview. - Ajakaiye, O; Dercon, S (OUP, 2008)
This volume revisits the risks posed to sustainable development in Africa by natural disasters, climate change and political violence, contributing to the evidence base and identifying key issues that would warrant further research. It offers a modest contribution to discussions on human security-development nexus drawing on evidence from macro- and micro-economic analysis. A key message is that in order to do a more rigorous analysis of the risks posed by key elements of human security to development in Africa, considerable effort should be devoted to data collection. Meanwhile, the evidence available suggest that the effects of these risks on development can be large and long lasting. In terms of policy responses, the insight is that the impact of some of these risks on human development can be mitigated through innovative insurance and financial mechanisms. However, all the contributions to this volume stress the imperative of strong and effective institutions in managing the impact of some of these risks, especially those related to political violence and climate change, as well as reducing the risks themselves.